Decree no 116 of the year 2017 Concerning the rules for importing Drugs, Raw Materials, Biologicals, Formula Milks and Medical Supplies From Reference and Non-Reference Countries - Egypt (2025)
Ministerial of health and population decree no. 116 of the year 2017 concerning the rules for importing drugs, raw materials, biologicals, formula milks and medical supplies from reference and non-reference countries – وزارة الصحة والسكان قرار رقم 116 لسنة 2017 بشأن قواعد استيراد الأدوية والخامات والمستحضرات الحيوية وألبان الأطفال والمستلزمات الطبية من الدول المرجعية وغير المرجعية